Conservative Treatment of Closed Fracture Shaft Humerus in Adult Patients - Majeed, Ghadeer . H; Al- Iedani, Mohammed S.; Kalif, Ismaeel (AL-Kindy College Medical Journal, 2013)
Background: Fractures of the humeral shaftaccounting for approximately 3% of allfractures. There is a wide array of goodoptions for their treatment and controversyover the best methods. Although goodtechniques of osteosynthesis are available, theaim of this article is toemphasize on the benefitand good outcome of conservative treatmentfor properly selected cases to decrease the costand avoid the complications of surgery.